Quantification of Phenolic Compounds from Fadogia agrestis and Dietary Supplements using UHPLC-PDA-MS - Avula, Bharathi; Bae, Ji-Yeong; Raman, Vijayasankar; Fantoukh, Omer I.; Wang, Yan-Hong; Osman, Ahmed G.; Wang, Mei; Ali, Zulfiqar; Khan, Ikhlas A. (Planta Medica, 2019)
Fadogia agrestis is used in traditional African medicine as an analgesic and for anti-inflammatory and aphrodisiac activities. An ultra-high-performance liquid chromatography method was developed for the determination of 11 chemical constituents from roots and aerial parts of F. agrestis. The separation was achieved within 7 min by using C-18 column material and a water/acetonitrile mobile phase, both containing 0.1% formic acid gradient system with a temperature of 45 °C. The method was validated for linearity, repeatability, limits of detection, and limits of quantification. The limits of detection of phenolic compounds were found to be in the range from 0.025 to 0.1 µg/mL. The wavelengths used for quantification with the photodiode array detector were 238, 254, 291, and 325 nm. Twelve of 17 dietary supplements contained phenolic compounds in the range from 0.3 to 2.7 mg/d. The phenolic compounds were not detected in five dietary supplements. Liquid chromatography-mass spectrometry coupled with electrospray ionization interface method is described for the identification and confirmation of compounds from plant samples and dietary supplements claiming to contain F. agrestis. This method involved the use of [M + H]+ and [M + Na]+ ions in the positive mode and [M − H]− ions in the negative mode with extractive ion monitoring. The developed method is simple, economic, rapid, and especially suitable for quality control and chemical fingerprint analysis of F. agrestis.
Keywords: Fadogia agrestis; Rubiaceae; phenolic compounds; dietary supplements; UHPLC-PDA-MS; quality control